Gonad development and diets of silver sillago (Sillago sihama) in the Marudu Bay, Sabah - Yusoff, Mohd. Yumnihadi (2013)
Studies on the spawning period and diets preference of Sillago sihama was conducted from December 2012 to September 2013. The objectives of the study were to estimate the spawning period, diets preference and feeding habits by S. sihama. A total of 188 samples of S. sihama were collected monthly in the Marudu Bay, Sabah. Each fish sample was dissected to collect the male or female gonad and stomach. No specific breeding period of S. sihama was seen throughout the study period. The spawning time was estimated to occurred from the peak to lower GSI value in November-December (1.17%), February-March (2.08%), April-May (2.88%) and July-August (1.11%) and the highest peak spawning time was observed between July to August. The lowest GSI value indicated the spent stage of the gonad while the higher GSI value recorded in February, April, June and July indicated the maturation period of the gonad of S. sihama. The diet composition were group into twelve major food items comprised of phytoplankton, seaweed fragment, zooplankton, animal fragment, annelid, nematode, foraminifera, mollusca, shrimp, crab, sand and mud and unidentified item. In term of diet composition, the most preferable food items of S. sihama were phytoplankton (26.95%), followed by animal fragment (26.65%), sand and mud (20.73%), nematode (5.75%), unidentified item (5.61%), zooplankton (5.24%), annelid (5.19%), mollusca (1.56%), shrimp (0.78%), seaweed fragment (0.71%), foraminifera (0.42) and crab (0.41%). Phytoplankton, animal fragment, sand and mud and nematode could be regarded as the important diets for S. sihama. On the basis of food composition found, it can be conclude that S. sihama is omnivorous species.